Cerebral Autoregulation and Conventional and Diffusion Tensor Imaging Magnetic Resonance Imaging in Neonatal Hypoxic-Ischemic Encephalopathy - Carrasco, Melisa (Pediatr Neurol, 2018)
BACKGROUND: Deviation of mean arterial blood pressure (MAP) from the range that optimizes cerebral autoregulatory vasoreactivity (optimal MAP) could increase neurological injury from hypoxic-ischemic encephalopathy (HIE). We tested whether a global magnetic resonance imaging (MRI) brain injury score and regional diffusion tensor imaging (DTI) are associated with optimal MAP in neonates with HIE. METHODS: Twenty-five neonates cooled for HIE were monitored with the hemoglobin volume index. In this observational study, we identified optimal MAP and measured brain injury by qualitative and quantitative MRIs with the Neonatal Research Network (NRN) score and DTI mean diffusivity scalars. Optimal MAP and blood pressure were compared with brain injury. RESULTS: Neonates with blood pressure within optimal MAP during rewarming had less brain injury by NRN score (P = 0.040). Longer duration of MAP within optimal MAP during hypothermia correlated with higher mean diffusivity in the anterior centrum semiovale (P = 0.008) and pons (P = 0.002). Blood pressure deviation below optimal MAP was associated with lower mean diffusivity in cerebellar white matter (P = 0.033). Higher optimal MAP values related to lower mean diffusivity in the basal ganglia (P = 0.021), the thalamus (P = 0.006), the posterior limb of the internal capsule (P = 0.018), the posterior centrum semiovale (P = 0.035), and the cerebellar white matter (P = 0.008). Optimal MAP values were not associated with the NRN score. CONCLUSIONS: The NRN score and the regional mean diffusivity scalars detected injury with mean arterial blood pressure deviations from the optimal MAP. Higher optimal MAP and lower mean diffusivity may be related because of cytotoxic edema and limited vasodilatory reserve at low MAP in injured brain. DTI detected injury with elevated optimal MAP better than the NRN score.